2017
DOI: 10.4236/jilsa.2017.91002
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Intelligent Learning Emotion System

Abstract: Nowadays, millions of users use many social media systems every day. These services produce massive messages, which play a vital role in the social networking paradigm. As we see, an intelligent learning emotion system is desperately needed for detecting emotion among these messages. This system could be suitable in understanding users' feelings towards particular discussion. This paper proposes a text-based emotion recognition approach that uses personal text data to recognize user's current emotion. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For ISEAR dataset, although the biggest number of sentences in train data is anger, the system recognizes joy and fear better than any other emotion categories. Although we cannot explain why our system performs well on joy and fear emotion categories, other researchers also reported that they obtain the best performance in another category instead of anger category [14], [28]. Figure 7 and 8 shows obtained confusion matrix plot from those datasets.…”
Section: Categorical Emotion Recognitionmentioning
confidence: 86%
See 2 more Smart Citations
“…For ISEAR dataset, although the biggest number of sentences in train data is anger, the system recognizes joy and fear better than any other emotion categories. Although we cannot explain why our system performs well on joy and fear emotion categories, other researchers also reported that they obtain the best performance in another category instead of anger category [14], [28]. Figure 7 and 8 shows obtained confusion matrix plot from those datasets.…”
Section: Categorical Emotion Recognitionmentioning
confidence: 86%
“…Significant research have been conducted on text emotion recognition, from text corpus construction [5], [6] to feature extraction [7], classifier development [14], [16] and its application [4]. Strapparava and Mihalcea has developed text corpus for text emotion task [5] and presented an explanation of their corpus annotation process in [8].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Razek and Frasson, used Dominant Meaning Classifier (DMC) to recognize emotion from text [46]. A dominant tree is trained on the ISEAR dataset to form seven emotion classes, joy, fear, anger, sadness, disgust, shame, and guilt, which is in line with Carroll [29] discrete emotions.…”
Section: Yasmina Et Al Used Point Wise Mutual Information (Pmi) To Cmentioning
confidence: 99%
“…Nowadays, emotion mining based on the social media has become one of the most important tasks in optimizing human-computer interaction. e textual sentiment analysis published by social media such as microblog has also attracted widespread attention, and many related research studies have been conducted [1][2][3][4]. Nevertheless, the emotion information contained in text is limited, and there are several fetters on the identification of technical terms in specific fields.…”
Section: Introductionmentioning
confidence: 99%